A global meta-analysis on the ecological drivers of forest restoration success - Renato Crouzeilles (Nature Portfolio, 2016)
Restoration of degraded ecosystems is known to enhance biodiversity and vegetation structure. Using a global meta-analysis, Crouzeilles et al. identify the drivers of restoration success in forest ecosystems at both the local and landscape scales.